'NO OUTLET': a critical visual analysis of neoliberal narratives in mediated geographies. (February 2017) - Gutsche, Robert E; Shumow, Moses
This article turns to Miami, Florida's (USA) Upper Eastside – an eclectic stretch of about 20 city blocks in one of the nation's 'global cities' – for a critical visual analysis that uses mapping and photography to explore how neoliberalism is communicated. With an approach that considers geography as a visual 'vernacular landscape', this research further supports the role of visual communication as a means to reveal deeper meanings of geography, particularly in terms of identifying ideological qualities of the neoliberal project that are often hidden in plain view. The authors' photographs and maps supply data for this article, which are then read through the process of 'geosemiotics'.